(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Mahasweta Devi is one of those contemporary writers who deals with all these forms of oppression in her work. What distinguishes Mahasweta Devi from other writers, both male and female, is the zeal of activists in her writings, representing her involvement in the problems of the underprivileged. It gives voice to the voiceless by exposing the different forms of oppression inherent in Indian society and also fighting for their rights. Mahasweta Devi ’s approach to oppression is unique, because while most women writers deal with the gender oppression of middle-class or upper-class women, Devi deals with the issue of gender oppression embodied within their class and caste dichotomies. Her activist writings, in the form of essays, short storeys, plays and novels, explore the trident forms patterns of oppression — class, caste, and gender oppression.